2019
DOI: 10.14716/ijtech.v10i4.1320
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Musculoskeletal Complaints among Hospital Nurses and Nursing Home Caregivers in Indonesia

Abstract: The jobs of hospital nurses and nursing home caregivers are often associated with risks of musculoskeletal disorders. Little is known, however, about the prevalence of such problems among nurses and caregivers in Indonesia. This study aims at determining the prevalence of musculoskeletal (MS) complaints experienced by caregivers in Indonesia and identifying relevant factors contributing to this problem. Standardized Nordic Questionnaires were distributed to 121 hospital nurses and nursing home caregivers, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Many factors were found to influence nurses’ physical health in the long-term care sector. Long shifts and physically taxing work combined to heighten the risk of musculoskeletal symptoms, including shoulder, lower back, neck, and joint pain ( Dhaini et al., 2016 ; Iridiastadi et al., 2019 ), which occurred significantly more often in long-term care than acute care ( OECD, 2020 ). Research set in Brazil and Estonia observed that musculoskeletal disorders were particularly prevalent amongst nurses in long-term care ( Mariano et al., 2015 ; Sepp et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors were found to influence nurses’ physical health in the long-term care sector. Long shifts and physically taxing work combined to heighten the risk of musculoskeletal symptoms, including shoulder, lower back, neck, and joint pain ( Dhaini et al., 2016 ; Iridiastadi et al., 2019 ), which occurred significantly more often in long-term care than acute care ( OECD, 2020 ). Research set in Brazil and Estonia observed that musculoskeletal disorders were particularly prevalent amongst nurses in long-term care ( Mariano et al., 2015 ; Sepp et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research set in Brazil and Estonia observed that musculoskeletal disorders were particularly prevalent amongst nurses in long-term care ( Mariano et al., 2015 ; Sepp et al., 2015 ). The most frequently reported types of physical injury in long-term care included back pain/injury, joint pain, and shoulder pain/injury ( Dhaini et al., 2016 ; Iridiastadi et al., 2019 ). An Estonian study measuring fatigue in nursing staff's thumb muscles after a shift suggested modern equipment as a solution to reducing nurses physiological stress in long-term care ( Sepp et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Musculoskeletal disorders not only affect physical and mental health, work performance, and quality of life and increase medical costs and social cost, but they can also decrease work competency and cause turnover [ [43] , [44] , [45] ]. Previous studies [ 8 , 9 , 46 ] also pointed out that musculoskeletal disorders are one of the main factors of turnover in nurse aides. Caring for patients requires the execution of many repetitive actions, and excessive force exertion or improper posture may lead to musculoskeletal soreness and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have highlighted the influencing factors of turnover behavior in nurse aides, some factors still lack an empirical basis. In this study, we compiled potential influencing factors found in the relevant literature or proposed by experts, which were classified as follows: personal socioeconomic background [ 4 , 5 ], workplace psychosocial hazards [ 2 ], worker health hazards [ 6 , 7 ], and musculoskeletal disorders [ 8 , 9 ]. These four factors are separately described below.…”
Section: Introductionmentioning
confidence: 99%
“…The patient-handling activities performed by hospital nurses are often associated with increased risk of musculoskeletal disorders or MSDs (Waters et al, 2007;Nelson et al, 2007;Iridiastadi et al, 2019). These are a group of disorders affecting the muscles, joints, tendons, ligaments, nerves, and bones, which are caused by strenuous physical activity in combination with poor posture (Batubara and Dharmastiti, 2017;Ribeiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%